Seasonal Field Calibration of Low-Cost PM2.5 Sensors in Different Locations with Different Sources in Thailand - Racha Dejchanchaiwong; Perapong Tekasakul; Apichat Saejio; Thanathip Limna; Thi-Cuc Le; Chuen‐Jinn Tsai; Guan-Yu Lin; John Morris (Atmosphere, 2023)
Low-cost sensors (LCS) have been increasingly deployed to monitor PM2.5 concentrations. More than 1500 LCS have been installed in Thailand to increase public awareness of air quality. However, performance of these sensors has not been systematically investigated. In this study, PM2.5 LCS were co-located next to a PM2.5 federal equivalent method (FEM) reference instrument at three Thai locations—in the north, center and northeast. We evaluated the performance of a PM2.5 LCS (PMS7003, Plantower) to understand the key factors affecting performance, including emission sources, relative humidity, temperature and PM2.5 concentration. Low PM concentration and high humidity levels had a significant impact on performance. Sensors in a high traffic emission area showed low correlation. The unadjusted PM2.5 LCS performance varied with locations. Errors were mainly observed at low concentrations. They significantly underestimated concentrations in congested urban environments. After calibration, accuracy was improved with multiple regression models. The performance of sensors only at Chiang Mai (CM) during the dry season and Ubon Ratchathani (URT) during the dry and wet seasons were acceptable with coefficient of variation: 5.8 ± 4.7–6.8 ± 5.0%, slope: 0.829–0.945, intercept: 1.12–5.49 µg/m3, R2: 0.880–0.934 and RMSE: 4.3–5.1 µg/m3. In the congested area in Bangkok (BKK), they underestimated concentrations of small particles.
Keywords: Air Quality Monitoring and Forecasting; Air Quality and Health Impacts; Vehicle emissions and performance